A careful reassessment of anthracycline use in curable breast cancer - Hurvitz, Sara Alsterlind; Mcandrew, Nicholas P.; Bardia, Aditya; Press, Michael F.; Pegram, Mark; Crown, John P.; Fasching, Peter; Ejlertsen, Bent; Yang, Eric H.; Glaspy, John A.; Slamon, Dennis J. (npj Breast Cancer, 2021)
It has been over three decades since anthracyclines took their place as the standard chemotherapy backbone for breast cancer in the curative setting. Though the efficacy of anthracycline chemotherapy is not debatable, potentially life-threatening and long-term risks accompany this class of agents, leading some to question their widespread use, especially when newer agents with improved therapeutic indices have become available. Critically assessing when to incorporate an anthracycline is made more relevant in an era where molecular classification is enabling not only the development of biologically targeted therapeutics but also is improving the ability to better select those who would benefit from cytotoxic agents. This comprehensive analysis will present the problem of overtreatment in early-stage breast cancer, review evidence supporting the use of anthracyclines in the pre-taxane era, analyze comparative trials evaluating taxanes with or without anthracyclines in biologically unselected and selected patient populations, and explore published work aimed at defining anthracycline-sensitive tumor types.
CRIS-Team Scopus Importer:2021-10-22